Heart rate variability during head‐up tilt shows inter‐individual differences among healthy individuals of extreme Prakriti types - Ritu Rani; Prathiban Rengarajan; Tavpritesh Sethi; Bharat Krushna Khuntia; Arvind Kumar; Deep Shikha Punera; Deepika Singh; Bhushan Girase; Ankita Shrivastava; Sanjay K. Juvekar; Bala Pesala; Mitali Mukerji; et al. (Physiological Reports, 2022)
Abstract Autonomic modulation is critical during various physiological activities, including orthostatic stimuli and primarily evaluated by heart rate variability (HRV). Orthostatic stress affects people differently suggesting the possibility of identification of predisposed groups to autonomic dysfunction‐related disorders in a healthy state. One way to understand this kind of variability is by using Ayurvedic approach that classifies healthy individuals into Prakriti types based on clinical phenotypes. To this end, we explored the differential response to orthostatic stress in different Prakriti types using HRV. HRV was measured in 379 subjects(Vata = 97, Pitta = 68, Kapha = 68, and Mixed Prakriti = 146) from two geographical regions(Vadu and Delhi NCR) for 5 min supine (baseline), 3 min head‐up‐tilt (HUT) at 60°, and 5 min resupine. We observed that Kapha group had lower baseline HRV than other two groups, although not statistically significant. The relative change (%Δ1&2) in various HRV parameters in response to HUT was although minimal in Kapha group. Kapha also had significantly lower change in HR, LF (nu), HF (nu), and LF/HF than Pitta in response to HUT. The relative change (%Δ1) in HR and parasympathetic parameters (RMSSD, HF, SD1) was significantly greater in the Vata than in the Kapha. Thus, the low baseline and lower response to HUT in Kapha and the maximum drop in parasympathetic activity of Vata may indicate a predisposition to early autonomic dysfunction and associated conditions. It emphasizes the critical role of Prakriti‐based phenotyping in stratifying the differential responses of cardiac autonomic modulation in various postures among healthy individuals across different populations.